Impact of rice wine-steamed Cistanche deserticola polysaccharides on intestinal flora and immunological modulation in immunosuppressive mice induced by cyclophosphamide - Lian, Jing; Zhu, Yuexin; Hu, Qiushi; Dong, Kexu; Peng, Zihang; Feng, Yurou; Ling, Na; Yu, Caina; Liu, Pengpeng; Lei, Xuefei; Shi, Ji; Jia, Tianzhu (Frontiers in Immunology, 2026)
IntroductionCistanche deserticola, a valued medicinal and food homologous material in traditional Chinese medicine, is renowned for enhancing immunity and protecting the mucosal barrier, with polysaccharides considered its primary active components. Raw material requires processing for optimal efficacy, yet most studies focus on unprocessed polysaccharides (RCP). This study investigates how traditional rice-wine processing alters the polysaccharides (WCP) and their immunomodulatory effects.MethodsThe physicochemical properties of RCP and WCP were characterized using SEM, HPGPC, FT-IR, and GC-MS. Immunosuppressed mice induced by cyclophosphamide (CTX) were used as an in vivo model. Immune function was assessed via body weight, organ indices, serum immunoglobulins (IgA, IgM), cytokines (IL-2, IFN-γ), spleen histopathology, and T cell subsets (CD4+/CD8+). Gut microbiota composition was analyzed by 16S rRNA sequencing, and short-chain fatty acid (SCFA) levels were measured.ResultsWine processing significantly modified the polysaccharides, increasing polysaccharide content, markedly reducing molecular weight, and altering monosaccharide composition in WCP. In CTX-induced mice, WCP administration showed superior immunomodulatory effects: it significantly improved spleen and thymus indices, elevated serum IL-2, IFN-γ, IgA, and IgM levels, and increased the CD4+/CD8+ ratio. Furthermore, WCP restored CTX-disturbed intestinal SCFA levels and positively modulated gut microbiota by increasing Bacteroidetes and beneficial probiotics, lowering the Firmicutes/Bacteroidetes ratio, and suppressing pathogenic bacteria.DiscussionTraditional rice-wine processing optimizes the molecular structure of Cistanche polysaccharides and significantly enhances their immunomodulatory efficacy in a cyclophosphamide-induced immunosuppression model. The enhanced activity is associated with marked improvements in gut microbiota composition and systemic immune parameters, suggesting involvement of the gut-immune axis. These findings provide a scientific basis for the traditional processing method and support the further development of processed Cistanche as a potential functional food or therapeutic agent.